2020
DOI: 10.5539/elt.v13n11p75
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Practices of English Language Teaching: A Meta-Analysis of Meta-Analyses

Abstract: This meta-analysis aims at investigating the impact of English language teaching practices on language outcomes. The literature search yielded 90 meta-analyses that were published between January, 1995 and December, 2019. The current study analyzed 90 meta-analysis and these studies comprised 3496 studies, 7870 effect sizes and nearly 700,000 students. Three moderator variables were examined: year of publication, setting and educational level. The results showed that a) language learning strategies had medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…It can be seen from the assumptions that considering the diversified training objectives, when the calculation length is greater than the support value of itemset s, it is not necessary to continue to solve the itemset with length greater than s. Therefore, through the support calculation, the information with scale greater than s in the resource library can be deleted while determining the composition of itemset s; that is, the information with more complex or large amount of calculation can be deleted and facilitate the efficient mining of multilevel input-oriented English teaching model in the later stage [16,17].…”
Section: Support Calculation Of Data Items In the Multilevel Inputmentioning
confidence: 99%
“…It can be seen from the assumptions that considering the diversified training objectives, when the calculation length is greater than the support value of itemset s, it is not necessary to continue to solve the itemset with length greater than s. Therefore, through the support calculation, the information with scale greater than s in the resource library can be deleted while determining the composition of itemset s; that is, the information with more complex or large amount of calculation can be deleted and facilitate the efficient mining of multilevel input-oriented English teaching model in the later stage [16,17].…”
Section: Support Calculation Of Data Items In the Multilevel Inputmentioning
confidence: 99%
“…One simple way to address this issue and improve the discoverability of replication studies is to use explicit labeling in the title and abstract (see In contrast, a recent meta-analysis of meta-analyses in English language teaching showed that 84 of the 90 meta-analyses (or 93%) included the label 'metaanalysis' or 'research synthesis' in the title (see Alsowat, 2020). By not using the label 'replication' in the study title, the discoverability of replications and their potential impact on the field are being limited.…”
Section: Improving the Discoverability Of Replication Studiesmentioning
confidence: 99%
“…For example, in Marsden et al's (2018) review of self-labeled replication studies in L2 research, only 13 of the 63 published articles (or 21%) included the label "replication" in the title. In contrast, a recent meta-analysis of meta-analyses in English language teaching showed that 84 of the 90 meta-analyses (or 93%) included the label "meta-analysis" or "research synthesis" in the title (see Alsowat, 2020). By not using the label "replication" in the study title, the discoverability of replications and their potential impact on the field are being limited.…”
Section: Improving the Discoverability Of Replication Studiesmentioning
confidence: 99%